Active Utilization of Linear Cultural Heritage Based on Regional Ecological Security Pattern along the Straight Road (Zhidao) of the Qin Dynasty in Shaanxi Province, China - Han Li; Tian Zhang; Xiaoshu Cao; Lingling Yao (Land, 2023)
Linear cultural heritage—a heritage system spanning time and space—is a large-scale cultural settlement that accommodates various heritage types. Here, we comprehensively explored the Straight Road (Zhidao) of the Qin Dynasty in Shaanxi Province, China, as a gene of traditional cultural connotations and geographical features, and provided holistic conservation strategies and effective utilization paths. From an ecological security pattern perspective, 4399.89 km2 of ecological sources and 19 ecological nodes were identified based on the importance of four ecosystem services—carbon sequestration and oxygen release, water conservation, habitat maintenance, and soil retention. Then, 45 ecological corridors with a total length of 2938.49 km were determined using the minimum cumulative resistance model. The intersections of ecological corridors were distinguished and the key areas of cultural landscape construction were extracted by taking into account the spatial distribution of existing relics as well as the spatial network relationship of prohibited-development areas and existing gray corridors (roads), blue corridors (rivers), and green ecological corridors (shade zones, green belts, recreational greenways). A plan was proposed to construct 98.45 km2 of new parks (country parks: 28.38 km2, forest parks: 70.07 km2) and 101.26 km of new landscape corridors (urban type: 32.08 km, countryside type: 26.49 km, ecological type: 42.69 km). Multilevel landscape complexes should be built to form a functional and networked ecological–cultural spatial structure system. Findings of this study could provide ecological ideas for promoting the reservation and active utilization of linear cultural-heritage corridors on a regional scale.